Probiotics, could be functional foods? - Rogulska, Karolina; Kapczuk, Patrycja; Zioło, Anna; Sarna, Angela; Jacek, Roksana; Grzeszczak, Konrad (Journal of Education, Health and Sport, 2022)
Research on functional food (FF) began in the 1980s in Japan, although the term appeared in the journal Nature in 1993. Functional foods can be natural or FF are created via the addition or removal of certain ingredients in technological processes. These treatments are aimed at obtaining food products that have health-promoting effects, including anti-inflammatory and antioxidant effects. The best representative example of functional food is probiotic food. According to World Health Organization (WHO) probiotics are live micro-organisms that, in adequate amounts, provide health benefits to the host. This has the effect of inhibiting the pathogenic bacterium Escherichia coli and E. coli translocation in the gastrointestinal tract.. In addition, it can also influence the repair of the damaged intestinal barrier. Probiotics can also improve the host immune system via strong adherence and colonisation of the gut. This results in the secretion of cytokines and chemokines, which are involved in immune processes. More than that, probiotics have the ability to produce peptides directed against microorganisms. These include lantibiotics, bacteriolysins and peptide bacteriocins. The review presented shows that probiotics as functional foods have an important role in human health. Their intake has many benefits and their appropriate use can significantly improve the comfort of a person’s life.